Anemia and undernutrition among children aged 6–23 months in two agroecological zones of rural Ethiopia - Roba KT; O'Connor TP; Belachew T; O'Brien NM (Dove Medical Press, 2016)
Kedir Teji Roba,1 Thomas P O’Connor,2 Tefera Belachew,3 Nora M O’Brien2 1School of Nursing and Midwifery, College of Health and Medical Science, Haramaya University, Harar, Ethiopia; 2School of Food and Nutritional Science, University College Cork, Cork, Ireland; 3Department of Population and Family Health, College of Public Health and Medical Sciences, Jimma University, Jimma, Ethiopia Background: Child malnutrition during the first 1,000 days, commencing at conception, can have lifetime consequences. This study assesses the prevalence of anemia and undernutrition among children aged 6–23 months in midland and lowland agroecological zones of rural Ethiopia.Methods: Cross-sectional data examining sociodemographic, anthropometry, hemoglobin levels, and meal frequency indicators were collected from 216 children aged 6–23 months and their mothers randomly selected from eight rural kebele (villages).Results: Of 216 children, 53.7% were anemic, and 39.8%, 26.9%, and 11.6% were stunted, underweight, and wasted, respectively. The prevalence of anemia was higher in the lowland agroecological zone (59.5%) than the midland (47.6%). Among those children who were stunted, underweight, and wasted, 63.5%, 66.7%, and 68.0% were anemic, respectively. Child anemia was significantly associated with the child not achieving minimum meal frequency, sickness during the last 2 weeks before the survey, stunting and low body mass index, and with maternal hemoglobin and handwashing behavior. The prevalence of stunting was higher in the lowland agroecological zone (42.3%) than the midland (36.2%). The predictors of stunting were age and sex of the child, not achieving MMF, maternal body mass index, and age. As maternal height increases, the length for age of the children increases (P=0.003).Conclusion: The overall prevalence of anemia and undernutrition among children aged 6–23 months in these study areas is very high. The prevalence was higher in the lowland agroecological zone. Health information strategies focusing on both maternal and children nutrition could be sensible approaches to minimize stunting and anemia. Keywords: child anemia, child stunting, lowland, midland, agroecological zone, rural Ethiopia